350 LONGITUDINAL MONITORING OF TACROLIMUS EXPOSURE IN PEDIATRIC RENAL TRANSPLANT RECIPIENTS. (1st January 2006) - Lee, M. N.; Butani, L.
Abstract : Due to the narrow therapeutic index of calcineurin inhibitors, monitoring of drug exposure is recommended after transplantation (Tx). Unlike cyclosporine, tacrolimus (T) trough levels supposedly have better correlation with the area under the time concentration curve (AUC) of the drug, although pediatric data are scant. The purpose of our study was to longitudinally monitor the AUC of T using a validated abbreviated method and to compare the T trough levels with the AUC. Renal transplant patients, who were transplanted between 8/01 and 6/05, were monitored prospectively. Trough, 2 hr, and 4 hr samples for serum T levels were drawn at 1, 3, 6, 9, and 12 months after Tx. Subjects were analyzed in two separate groups, based on duration of prednisone therapy: the standard protocol group (SP) received long-term prednisolone ( n = 15) and the steroid-minimization (SM) group received only 3 days of prednisolone ( n = 5). The immediate, 1- and 3- to 12-month target troughs for T were set at 10-15, 5-10, and 5 ng/mL respectively. Simple descriptive statistics and the Pearson correlation test were performed using SPSS . The mean age at Tx was 8.5 years. The median AUCs for the 2 cohorts are outlined in the Table. The correlation between T trough and AUCs was better in the SM ( r = .96) versus the SP cohort ( r = .84) and was most exaggerated in the first month (SM r = .91 versus SF r = .53). The correlation between the dose of T and the AUC was poor at all times in both groups ( r = 0.2-0.4). In conclusion, except for the first month in the SP cohort, T trough levels correlate well with the AUC in pediatric renal transplant patients. In all patients receiving T, there is marked interindividual variation in the AUC of T for a given dose. Based on this, we feel it is useful to follow the abbreviated AUC in patients taking prednisone. In the SM population, the concordance between the AUC and T trough should be assessed in each patient before relying on the T trough as a marker of exposure. Albeit limited in number, our study provides clinicians with the first longitudinal data in children on T AUCs corresponding to target trough goals at different time points after renal Tx.